Excessive Evaluation Anxiety (XEA): The Last Two Decades - Nia Seunghye Kang; Katherine Moreau (The Evaluation Center at Western Michigan University, 2023)
Background: Excessive evaluation anxiety (XEA) refers to disproportionate or increased evaluation anxiety among those affected by evaluation (e.g., stakeholders) characterized by the sole presence of negative consequences. It can compromise evaluator-stakeholder relationships, presenting as a barrier for program evaluation. Moreover, XEA can both cause and be caused by resistance to evaluation, which is an interrelated topic that shares many common causes, characteristics, and mitigation strategies. The participatory and interactive nature of modern evaluation approaches can exacerbate the presence of XEA. However, researchers have not explored the current state of literature on XEA. Purpose: To explore the current state of the literature on XEA over the past 20 years. Setting: Not applicable. Intervention: Not applicable. Research Design: Literature review. Data Collection and Analysis: We conducted a literature search of Academic Search Complete, Web of Science, and Scopus. We complemented the database search by a journal search of the American Journal of Evaluation, Evaluation, and the Canadian Journal of Program Evaluation. We then conducted a thematic analysis of the articles that met the inclusion criteria. Findings: Upon review of the articles, we identified four main themes in the literature related to XEA. Specifically, XEA: leads to poor evaluator-stakeholder relationships; is influenced by cultural factors; can be mitigated through the development of interpersonal skills; and can be mitigated through a systematic and evidence-based approach to evaluation. Keywords: Excessive evaluation anxiety, resistance to evaluation, program evaluation, evaluator-stakeholder relationships